Autopercepción corporal, nivel socioeconómico y estado nutricional en adolescentes de 15 a 17 años de la I.E. Mariscal Oscar R. Benavides – iquitos 2023 - Graicht Murayari, Claudia Priscila (2024)
The objective of this study was to determine the relationship between body self- perception and socioeconomic level with nutritional status in adolescents 15 to 17 years of age from the I.E. Marshal Oscar R. Benavides of the Iquitos district. The research had a descriptive and correlational approach, not an experimental, cross- sectional quantitative approach. The sampling was stratified probabilistic. The sample was made up of 215 adolescents from 15 to 17 years old. Anthropometric and biochemical evaluations were carried out, as well as filling out questionnaires. 72.09% of adolescents had a normal body mass index for their age; however, 14.42% were also found to be thin, 10.23% overweight and 3.26% obese. 3.72% presented high risk and only 1.4% presented very high risk according to abdominal perimeter. E 39.53% of adolescents presented an optimal level of body fat, 5.12% a very high level, 19.53% a high level, 27.91% a moderate level, 6.51% low high and 1.40% very low. On the other hand, 15.35% had mild anemia, 5.12% had moderate anemia and 1.40% had severe anemia; and 93.49% of adolescents had glucose within normal values. Regarding body self perception, 58.14% of adolescents are not worried about their body self-perception, 17.21% presented slight concern, 16.28% moderate concern, and 8.37% high concern. It was concluded that there is a significant statistical relationship between socioeconomic level and body self-perception with body mass index, anemia, body mass, glucose and abdominal circumference.